Eligibility to drive and neurology: the how and the why. Issue 4 (17th May 2022) - Rees, Jeremy; Cooper, Paul; Cruickshank, Garth; Jenkins, Nick
Abstract : Driving is an integral part of adult life and losing a driving licence is potentially a major problem. Many neurological conditions may impact on driving, either by increasing the risk of a sudden disabling event or by affecting cognition, vision, reaction speed, motor coordination, peripheral sensation or visuospatial processing. In the UK, the Drivers Medical Group of the Driver and Vehicle Licensing Agency (DVLA) decides whether an individual's medical condition meets the appropriate standards for driving. The licensing decision rests with the DVLA and is not at the clinician's discretion. However, clinicians must inform patients of their legal obligations towards the DVLA and how their neurological symptoms may restrict their driving. We discuss risk assessment, how chronic disabling neurological disease may impact on driving and the general principles of applying medical standards for fitness to drive. We also highlight how legal driving eligibility varies around the world. Finally, we discuss the practical applications relating to a specific case.